Microfinance in Russia : Broadening Access to Finance for Micro and Small Entrepreneurs - Bossoutrot, Sylvie K. (Washington, DC: World Bank, 2012)
Microfinance institutions of four types have emerged to meet the unfulfilled financing needs of micro-entrepreneurs: commercial banks, specialized NGO-type microfinance institutions, membership-based institutions (such as rural cooperatives and credits unions), and public funds. All four types have enjoyed significant growth in Russia in the past five years, but the industry is still at an early stage of development. Demand appears to far outweigh supply.